PENDAMPINGAN PEMBUATAN AKTIVITAS PEMBELAJARAN BERKONTEKS BUDAYA MATERI GEOMETRI DI KOTA PAGARALAM - Lisnani, Lisnani; Indra Putri, Ratu Ilma; Zulkardi, Zulkardi; Kurniadi, Elika; Rawani, Dewi; Gustiningsih, Tria; Malalina, Malalina; Herlina, Rini; Rahayu, Chika; Sari, Arika; Septimiranti, Delia; Inderawati, Rita (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. Integrated Community Service (PKM) is a form of service that accommodates a series of activities as a whole. Assistance in making RPP independent learning in a cultural context on geometry material for teachers of SMP, SMA and SMK in Pagar Alam. The purpose of this service activity is to assist teachers in designing learning activities the use of cultural contexts, especially on geometry material. The participants of the integrated PKM activity consisted of 49 people but at the time of mentoring it was only attended by 28 participants. The service activity was carried out for 2 days, on October 5-6, 2021. The methods used during this mentoring activity were the method of presentation, discussion, interactive question and answer, and recitation. The data collection technique used a questionnaire/questionnaire given through a google form consisting of an activity evaluation questionnaire and a participant satisfaction questionnaire for all integrated PKM activities. The results of this service activity showed that 73.48% of the participants had understood the material presented by the resource person. In addition, participants stated that this activity was useful for them, especially in making learning activitis independent in learning to use certain contexts. Abstrak. Pengabdian Kepada Masyarakat (PKM) yang terintegrasi merupakan sebuah bentuk pengabdian yang mengakomodir serangkaian kegiatan secara keseluruhan. Pendampingan pembuatan RPP merdeka belajar berkonteks budaya pada materi geometri bagi guru SMP, SMA dan SMK di Pagar Alam. Tujuan dari kegiatan pengabdian ini adalah membantu guru dalam merancang aktivitas pmebelajaran merdeka belajar yang sesuai melalui penggunaan konteks budaya terutama pada materi geometri. Peserta kegiatan PKM terintegrasi terdiri dari 49 orang tapi pada saat pendampingan hanya dihadiri oleh 28 orang peserta. Kegiatan pengabdian dilaksanakan selama 2 hari yaitu pada tanggal 5-6 Oktober 2021. Metode yang digunakan selama kegiatan pendampingan ini adalah metode presentasi, diskusi, tanya jawab interaktif, dan resitasi. Teknik pengumpulan data menggunakan angket/ kuesioner yang diberikan melalui google form yang terdiri dari angket evaluasi kegiatan dan angket kepuasan peserta terhadapa seluruh kegiatan PKM terintegrasi. Hasil dari kegiatan pengabdian ini menunjukkan bahwa adalah 73,48% peserta telah memahami materi yang disampaikan oleh narasumber. Di samping itu, peserta menyatakan bahwa kegiatan ini bermanfaat bagi mereka terutama dalam membuat aktivitas pembelajaran merdeka belajar menggunakan konteks tertentu.